Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.3382/ps.0690281
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Bioavailability of DL-Methionine Hydroxy Analog Compared to DL-Methionine

Abstract: Intestinal absorption of crystalline DL-methionine (DL-MET) and DL-methionine hydroxy analog calcium (DL-HMA) were determined in a true-digestibility-balance assay using cecectomized (CEC) and sham-operated conventional (CONV) cockerels. The treatments consisted of fasted birds and birds crop-intubated (CI) with 30 g of a corn-soybean meal basal diet (16% CP) supplemented with 0, .2, or .4% of DL-MET or equimolar levels of DL-HMA. There was no detectable free D-MET or L-MET or HMA in the excreta of fasted bird… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 13 publications
3
11
0
1
Order By: Relevance
“…This corresponds to a net absorption value of 90-8%, significantly lower than the net absorption of supplemental DL-methionine. Our value for the net absorption of MHA lies between that of Larbier (1988) and Han a al. (1990) for caecectomised birds.…”
Section: Methodsmentioning
confidence: 52%
See 2 more Smart Citations
“…This corresponds to a net absorption value of 90-8%, significantly lower than the net absorption of supplemental DL-methionine. Our value for the net absorption of MHA lies between that of Larbier (1988) and Han a al. (1990) for caecectomised birds.…”
Section: Methodsmentioning
confidence: 52%
“…The procedure was a modification of the Sibbald method as described by Han et al (1990). The cockerels were individually caged in a climatic chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the amount of L-Met and DL-HMB transported might be related to the differences in the mechanism by which HMB and L-Met are transported. In vivo chicken experiments have shown that the small intestine had similar capacities to absorb DL-HMB and L-Met (4,18,19). However, when the mechanisms of transport were examined, L-Met transport appeared to be Na ϩ -and energy-dependent carrier mediated and HMB transport appeared to be comprised of Na ϩ -independent and proton-dependent carrier mediated and diffusion (3,4,20).…”
Section: Resultsmentioning
confidence: 99%
“…The apparent digestibility of crystalline L-tryptophan is about 100 %, as for most crystalline amino acids (e.g. Han et al, 1988Han et al, , 1993Izquierdo et al, 1988;Chung and Baker, 1992). However, microbial degradation (e.g.…”
Section: Appendixmentioning
confidence: 99%